A randomised clinical trial of the effectiveness of home-based health care with telemonitoring in patients with COPD. (March 2015) - McDowell, Janet E; McClean, Sally; FitzGibbon, Francis; Tate, Stephen
We studied the effect of telemonitoring in addition to usual care compared to usual care alone in patients with chronic obstructive pulmonary disease (COPD). A total of 110 patients with moderate to severe COPD were recruited from a specialist respiratory service in Northern Ireland. Patients had at least two of: emergency department admissions, hospital admissions or emergency general practitioner (GP) contacts in the 12 months before the study. Exclusion criteria were patients who had any respiratory disorder other than COPD, or were cognitively unable to learn the process of monitoring. Patients were randomised to receive six months of home telemonitoring with usual care, or six months of usual care. The primary outcome measure was disease-specific quality of life, as measured by the St George's Respiratory Questionnaire for COPD patients (SGRQ-C). Of 100 patients completing the study, 48 patients were randomised to telemonitoring and 52 patients were randomised to the control group. The SGRQ-C scores improved significantly in the intervention group compared to usual care ( P = 0.001). The HADS anxiety score was significantly higher in the telehealth group compared to the usual care group ( P = 0.01). There were significantly more contacts with the Community Respiratory Team in the telemonitoring group compared to the control group ( P = 0.029). There were no significant between group differences in EQ-5D scores, HADS depression scores, GP activity, emergency department visits, hospital admissions or exacerbations. The total cost to the health service of the intervention over the 6-month study period was £2039, giving an estimated ICER of £203, 900. In selected patients with COPD, telemonitoring was effective in improving health-related quality of life and anxiety, but was not a cost-effective intervention.